Do personal attributes and an understanding of sarcasm and metaphor explain problematic experiences on the Internet? —A survey for the development of information literacy education tools— - Ichikawa, Hiroshi; TOYODA, Yuhiko; TAKEUCHI, Mika; TASHIRO, Mitsuteru; SUZUKI, Masao (Discoveries in Agriculture and Food Sciences, 2015)
The Internet today provides users with a great amount of convenience due to the improvement of tools and their functions, and the expansion in the numbers of users. However, with the expansion of both online content and time spent online, new and potential risks have emerged in this virtual space. A majority of Japanese students experience communication troubles over the Internet, and therefore higher education institutions have increased their efforts to reduce risks on the Internet by, for example, offering basic security education through information literacy programs. However, because of the number and variability of Internet risks, it is unlikely that these efforts have achieved satisfactory results. As one of the risk factors inducing troubles on the Internet, where users exchange information with other (anonymous) users, we examine the immaturity of the “theory of mind,” which is generally used to infer the conditions, viewpoints, and comprehension level of others. This study reports the results of a self-report questionnaire used to examine the problems or difficulties encountered on the Internet by young women in Japan. It focuses on the relationship between the comprehension of sarcasm and metaphor expressions, provided for the purpose of estimating the “theory of mind,” as well as of Internet terminology and the problematic experiences. The problems identified were roughly classified into four different categories: addictive Internet use, dishonest/illegal dealings, communication gaps, and shopping-related difficulties. Multiple regression analyses was conducted, aimed at identifying factors that could explain such problems. The results suggested that personal attributes and sensation-seeking tendencies, including social vulnerability and anxiety, and the understanding of sarcasm, metaphor expressions, and Internet terminology, might be significantly correlated with the problems experienced. On the basis of this study, proposals are made as to what areas should be focused on in information literacy education programs in the future.